Hakikat sila persatuan dalam adat Babukuk'ng suku Dayak Krio (Tinjauan filosofis terhadap nilai sila persatuan dalam budaya) - Parto, Hilarion Gerri (Jurnal Penelitian Humaniora, 2023)
Indonesia merupakan negara yang kaya akan adat, budaya, dan tradisi. Kekayaan ini merupakan suatu kebanggan bagi bangsa Indonesia. Hal ini menjadi sarana untuk menambah wawasan antara budaya yang satu dengan budaya yang lain dan menciptakan sesuatu yang baru. Kekayaan budaya ini pada akhirnya membentuk bangsa Indonesia menjadi bangsa yang sadar akan jati dirinya. Kemajemukkan adat, budaya, dan tradisi ini dapat pula menjadi pemecah kesatuan Indonesia. Sila ketiga yaitu sila persatuan tercerminlah nilai-nilai falsafah budaya bangsa Indonesia yang di dalamnya termuat berbagai cara hidup yang berbeda namun kaya akan keberagaman. Nilai persatuan menjadi konsep yang paling tinggi dalam babukuk'ng.  Metodologi yang digunakan dalam penelitian ini adalah metode kepustakaan. Penelitian ini menemukan bahwa Babukuk'ng memiliki nilai yang kaya akan falsafah kesatuan dan persatuan yang terikat erat dengan pancasila dan masih relevan untuk kehidupan kaum muda masa kini. Pancasila sebagai Falsafah perlu diaktualisasikan dengan cara kesediaan untuk saling menerima dalam perbedaan dengan kekhasan masing-masing.The essential of the precaution of union in the babukuk'ng tradition of the Dayak Krio  Indonesia is a country rich in customs, culture, and traditions. This wealth is a matter of pride for the Indonesian people. This is a means to add insight between one culture and another and create something new. This cultural wealth ultimately shapes the Indonesian nation into a nation that is aware of its identity. This plurality of customs, cultures, and traditions can also be a breaker for the unity of Indonesia. With this diversity, there can be the possibility of intolerance in every culture and the emergence of radicalism. The third principle, namely the principle of unity, reflects the philosophical values of the Indonesian nation's culture, which contains various ways of life that are different but rich in diversity. The value of unity is the highest concept in babukuk'ng. The method used was the library method. This study was aimed at finding out the essential of the precaution of union in the babukuk'ng tradision of Dayak Krio. The findings show that Babukuk'ng has values that are rich in the philosophy of unity and unity which is closely tied to Pancasila and is still relevant to the lives of today's youth. Pancasila as philosophy needs to be actualized using a willingness to accept each other in differences with their respective characteristics.